Grip strength as a predictor of Trait-Anxiety in university students - Huerta-Ojeda, Álvaro Cristian; Barahona-Fuentes, Guillermo; Galdames-Maliqueo, Sergio; Cáceres-Serrano, Pablo; Castillo, Nelson; Ortiz-Marholz, Paula (Universidad y Salud, 2021)
Introduction: Research has revealed that the implementation of physical activity programs improves mental health. However, there are still doubts about the relationship between muscle strength and the presence of psychosocial disorders such as anxiety and stress in the university student population. Objective: To study the association of a physical condition (grip strength) and the presence of Trait-Anxiety in female students. Materials and methods: An empirical research with a predictive associative strategy was conducted on a sample of 30 female undergraduate students. The predictor physical variables assessed were anthropometry, grip strength, and maximum oxygen consumption. Trait-Anxiety was evaluated using the State-Trait Anxiety Inventory (STAI). Statistical analysis was performed through ordinal logistic regression between predictor physical variables and level of Trait-Anxiety Results: Only grip strength was statistically significant (p=0.033). This analysis, expressed as Odds Ratio, assumes a 74.36% probability that the lower level of grip strength, the greater chances of having Trait-Anxiety. Conclusions: Grip strength is not only a physical parameter to detect cardiovascular risks and associated pathologies, but also it should be used to identify mental health disorders.